“Ibuku Adalah Guruku” : Model Pola Asuh Yokhebed - Muryati Muryati Muryati (Manna Rafflesia, 2022)
Education is a legacy of parents that needs to be accepted by everyone since childhood to live a successful and successful life in the future. The parties who play an important role as teachers or educators first and foremost for children are parents, especially mothers. However, the problem is that some mothers do not carry out these responsibilities so that their children become victims. This is what underlies the purpose of this study to explain one of the parenting styles of a mother named Jochebed who succeeded in becoming a teacher for Harun, Miriam, and Musa so that today's mothers can imitate him. The method used in this research is qualitatively based on a literature study. The results showed that Jochebed instilled faith and wisdom in them from an early age. This faith and wisdom were obtained by Jochebed from God because of his God-fearing attitude so that all his children, especially Moses, could become individuals of faith and wisdom in leading their people for the exodus from Egypt